ЯКІСНЕ ПРОЦЕСНЕ УПРАВЛІННЯ ПІДПРИЄМСТВОМ (International Journal of Innovative Technologies in Economy, 2018)
Matching the activity specifics, the method of the system constructing of business processes with the logical concept of the process approach inculcation at an enterprise is suggested and formally described.The process approach, which is used by many enterprises as the most progressive management tool, aimed at achieving results, has been examined and studied in detail.At the practical research level, it is found out that the systematic approach of mapping, performing, documenting, measuring, monitoring and controlling doth automated and non- automated processes determines the main role in the management of business processes in order to achieve the goals and the business strategies of the enterprise.